Ways of thinking about effective teaching - Vlasenko, Ludmila; Sulima, Irina (My University, 2011)
It is overviewed the main ways of learning foreign languages, and given their characteristics. It is described the technologies of learning foreign languages, their particularities during the process of foreign language studying.
Keywords: механізм; механизм; mechanism; навчання; технологія навчання; мова; изучение; технологии изучения; язык; learning; technologies of studying; language; кафедра ділової іноземної мови та міжнародної комунікації